Impact of the Southwark and Lambeth Integrated Care Older People's Programme on hospital utilisation and costs: controlled time series and cost-consequence analysis. Issue 3 (3rd March 2019) - Exley, Josephine; Abel, Gary A; Fernandez, José-Luis; Pitchforth, Emma; Mendonca, Silvia; Yang, Miaoqing; Roland, Martin; McGuire, Alistair
Abstract : Objectives: To estimate the impact on hospital utilisation and costs of a multi-faceted primary care intervention for older people identified as being at risk of avoidable hospitalisation. Design: Observational study: controlled time series analysis and estimation of costs and cost consequences of the Programme. General practitioner (GP)'s practice level data were analysed from 2009 to 2016 (intervention operated from 2012 to 2016). Mixed-effect Poisson regression models of hospital utilisation included comparisons with control practices and background trends in addition to within-practice comparisons. Cost estimation used standard tariff values. Setting: 94 practices in Southwark and Lambeth and 263 control practices from other parts of England. Main outcome measures: Hospital utilisation: emergency department attendance, emergency admissions, emergency admissions for ambulatory sensitive conditions, outpatient attendance, elective admission and length of stay. Results: By the fourth year of the Programme, there were reductions in accident and emergency (A&E) attendance (rate ratio 0.944, 95% CI 0.913 to 0.976), outpatient attendances (rate ratio 0.938, 95% CI 0.902 to 0.975) and elective admissions (rate ratio 0.921, 95% CI 0.908 to 0.935) but there was no evidence of reduced emergency admissions. The costs of the Programme were £149 per resident aged 65 and above but savings in hospital costs were only £86 per resident aged 65 and above, equivalent to a net increase in health service expenditure of £64 per resident though the Programme was nearly cost neutral if set-up costs were excluded. Holistic assessments carried out by GPs and consequent Integrated Care Management (ICM) plans were associated with increases in elective activity and costs; £126 increase in outpatient attendance and £936 in elective admission costs per holistic assessment carried out, and £576 increase in outpatient and £5858 in elective admission costs per patient receiving ICM. Conclusions: The Older People's Programme was not cost saving. Some aspects of the Programme were associated with increased costs of elective care, possibly through the identification of unmet need.